A Guide to the Otoliths of Southern Ocean Lanternfishes (Myctophidae) - Stevens, DW; Braid, HE; Meynier, L; Escobar-Flores, PC; Pinkerton, MH; Hopcroft, D; He, Y; Cherel, Y (Springer Science and Business Media LLC, 2024)
In the Southern Ocean, myctophids (family Myctophidae) are speciose, dominate the mesopelagic fish biomass, and are important in the diets of many fishes, squids, seabirds, and marine mammals. Consequently, they play a key role in carbon export and energy transfer from primary consumers to top predators. However, they are delicate and rarely found intact in predator stomachs, which makes them difficult to identify to species. Fortunately, their otoliths (sagittae) are mostly distinctive and therefore useful for species identification. Previous studies describing Southern Ocean myctophid otoliths were often limited by small sample sizes or focused on only a few species. To facilitate myctophid identifications in diet studies, we provide scanning electron microscope images of otoliths with brief descriptions for 37 species of Southern Ocean myctophids. The identities of problematic taxa were confirmed with DNA. Most species were found to have distinctive otoliths, which can be used to identify them to the species level. Large Gymnoscopelus piabilis otoliths comprised two types, which may represent different species. In addition, allometric equations are provided for 32 species to enable back calculation of fish size.
Keywords: 31 Biological Sciences; 3103 Ecology; 06 Biological Sciences; Marine Biology & Hydrobiology; 31 Biological sciences